Case Report: The woman with the big heart—an imaging-guided attempt of surgical reduction - Huenges, Katharina; Langguth, Patrick; Grothusen, Christina; Hoffmann, Grischa; Kapahnke, Julia; Haneya, Assad; Strotmann, Jörg; Cremer, Jochen (Frontiers in Cardiovascular Medicine, 2024)
In a female patient with acute cardiac decompensation, an auxiliary finding of a giant left atrium emerged. The surgical therapy of the atrial reduction, in addition to a mitral valve replacement and a coronary artery bypass grafting, is hereby presented.